2008
DOI: 10.1021/jf8016157
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Antioxidant and Anti-inflammatory Capacities of an Antioxidant-Rich Fruit and Berry Juice Blend. Results of a Pilot and Randomized, Double-Blinded, Placebo-Controlled, Crossover Study

Abstract: This study investigated the in vitro and in vivo antioxidant and anti-inflammatory properties of a juice blend (JB), MonaVie Active, containing a mixture of fruits and berries with known antioxidant activity, including açai, a palm fruit, as the predominant ingredient. The phytochemical antioxidants in the JB are primarily in the form of anthocyanins, predominantly cyanidin 3-rutoside, cyanidin 3-diglycoside, and cyanidin 3-glucoside. The cell-based antioxidant protection of erythrocytes (CAP-e) assay demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
2
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(156 citation statements)
references
References 24 publications
4
136
2
14
Order By: Relevance
“…Therefore, researchers are currently intensely focused on identifying antioxidant agents in plants that may protect against oxidative stress, including the Sasa species already used in alternative medicines (Jensen et al, 2008;Nakajima et al, 2003;Sood et al, 2009). This study evaluated the potential of using S. quelpaertensis leaf in nutraceuticals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers are currently intensely focused on identifying antioxidant agents in plants that may protect against oxidative stress, including the Sasa species already used in alternative medicines (Jensen et al, 2008;Nakajima et al, 2003;Sood et al, 2009). This study evaluated the potential of using S. quelpaertensis leaf in nutraceuticals.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicate that alkaloids and especially phenolics contained in medicinal plants have antioxidant and/or anti-inflammatory activity (Kao et Shaheen et al, 2005). Relationship between these two biological activities has also been established (Scalbert et al, 2005;Jensen et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, Jensen et al observed an increase in serum antioxidant levels and a reduction in lipid peroxidation following acute consumption of a 'polyphenol-enriched' açai-based beverage in a double-blind crossover [46]. More recently, the same authors reported slight improvements in the range of motion in arthritic patients following chronic consumption of the same product in a small non-controlled chronic study [47]. Udani et al observed significant reductions in plasma glucose, insulin and total cholesterol levels in a small non-controlled pilot study based on the chronic consumption of açai pulp in overweight volunteers [48].…”
Section: B Pbsmentioning
confidence: 88%